The Educational Workshops Importance of Students in Teaching-learning Deaf - Vons, Paula Cristina Cristina de Oliveira; Scopel, Janete Maria; Scur, Luciana (Scientia cum Industria, 2016)
Inclusive educational workshops can be used as teaching strategies for deaf students to integrate into society, allowing who are beneficiaries of diversified teaching methods, encouraging them to become active citizens in their rights and duties according to their potential. In order to build knowledge collectively, inclusive educational workshops were developed as the project methodology "The Natural Science Museum Goes to School: a proposal for inclusive education", which aimed to raise awareness among deaf students of the School of Special Education Helen Keller Caxias do Sul / RS on the importance of environmental preservation. The workshops allowed autonomy in the construction of knowledge as related theory with practice, creating situations where students stopped being only learning receivers. Workshops were held as hanging garden, environmental commitment, sensory garden, animals in origami, green puppet, puppet fish and terrarium. Participated in these activities students from 1st to 9th grades of elementary school and adult education, covering 102 participants. During the workshops inquiries were carried out, encouraging students to share prior knowledge with colleagues and enabling these acquire new environmental information, making meaningful learning. Pedagogical workshops should be used as support tools in the classroom, and worked in continuous and interdisciplinary way. As a result, deaf students feel valued and producers of their knowledge and will experience different activities recognizing the importance of learning to their daily lives. http://dx.doi.org/10.18226/23185279.v3iss3p139